NILAI PENDIDIKAN MORAL DAN KEMANUSIAAN DALAM PERIBAHAS JAWA BANTEN DI WILAYAH CILEGON – SERANG - Icah Maisah; Rudi Hartono (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study is to explore, discover, and preserve the Bantam Javanese proverb that is almost extinct. In addition, also to know the value of moral education and Humanity contained in Banten Javanese Proverb. This research started from September 2009 until June 2010 with content analysis techniques. This research focuses on moral education and humanitarian values in Java Banten proverbs. The instruments of this study are the researchers themselves and the sources through interview techniques. In technical analysis, researchers analyzed the value of moral education and the humanities in Java Banten proverbs carefully. Based on data collected/obtained, there are 218 proverbs which consist of 104 phrases, sayings 48, 45 parables, 14 imagery/parables, and a seventh rhyme. Once analyzed, from all the collected proverbs, which contain values and moral education as much as 39 that contains the value of humanity as much as seven proverbs. From the result, we can recognize the culture through the proverbs Java, Banten, and Sunda apart. In terms of meaning and values contained in the proverb, proverbs will add insight and a literary horizon for us. Is expected to stimulate research in finding more Proverbs other untapped. Their implications for learning in schools, namely teachers and students can use this as a learning proverbs appreciation of literature by examining the values contained therein, in addition to humanitarian values and moral education. For example social values, religious values, cultural values, economic values, ethical values, and aesthetic values.